Life under Nazi rule, reports by anti-fascists in occupied Europe, 1933-1945. (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2009)
These two newsletters published fortnightly by the ITF (i.e. Internationale Transportarbeiter Foederation) between 1933 and 1945. Based on analyses of other newspapers of the day, the editorial policy was to give information about social policy as well as reports from cadres working under cover. In this way it provides a unique insight into life under fascist regimes, focusing in particular on the working-class movement, organised labour and the growth of trade unions. In fact, it seems from the volume numeration introduced in 1936, that the editors came to view the two newsletters as one, but with a title change, as hinted at on p. 1 of the first issue of Fascism: It is more than a year ago since the first number of 'Germany under the Swastika' appeared, a publication in which we tried to show in a matter-of-fact manner the great contrasts between the promises and the deeds of the Hitler regime in Germany. There has been ample evidence that this publication was keenly appreciated both by the unions affiliated to the I.T.F. and far beyond on account of its contents, tendency and reliability. "That 'Germany under the Swastika' is to appear no more is not because there was no need for it. The opposite is the case unfortunately. Since its first appearance the number of countries where Fascism has risen to power, and then robbed the working classes of their rights and liberties, has increased by three, while in other countries Fascist influence has grown considerably.
Date range: 1933-1945.
Keywords: World War, 1939-1945 -- Economic aspects -- Germany; World War, 1939-1945 -- Occupied territories; Europe -- Economic policy; Europe -- Politics and government -- 1918-1945.; Europe -- History -- 1918-1945.; Fascism -- Europe -- History -- 1918-1945.